Overview of the new regulatory base for 2019–2020 on the decarbonisation of economy and its influence on the conditions of functconing of the ukrainian gas industry - Leshchenko (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
The purpose of this paper is to explore the influence of the new Ukrainian and European regulatory framework for 2019-2020 concerning the decarburization of economy of the functioning of Ukrainian gas industry.The paper provides an overview of the Ukrainian regulatory framework of 2019–2020 on the implementation of the system of monitoring, reporting, and verification of greenhouse gas emissions in our country. We also provide an overview of new European documents on the decarbonisation of economy, in particular, the European Green Deal, the EU Strategy for Reducing Methane Emissions, and the Hydrogen Strategy for Climate-Neutral Europe. We showed that these EU documents will exert a significant influence on the functioning of both the energy sector of our country as a whole and its part – gas industry.The paper shows that, under the existing plans of the development of energy sector in European countries in order to reach the state where there are no net emissions of greenhouse gases by 2050 and under conditions of fierce competition for sources and routes of gas supply to the European market, the most pressing problem confronting the gas transportation system of Ukraine is to optimize its structure with simultaneous replacement of outdated compressor equipment by modern one with lower carbon dioxide emissions, which will require a significant amount of investment. Under such conditions, it is necessary to study carefully the feasibility of introducing activities for the main transportation of gas under the action of Greenhouse Gas Trading System.We also showed that the reduction of methane emissions along the natural gas chain supply in accordance with the EU Strategy for the reduction of methane emissions is extremely important for Ukraine. In addition to the implementation of measures for reducing these emissions, it is necessary to attract attention to the development of national methods for estimating methane emissions and the use of national coefficients in the formation of the National Greenhouse gas emissions inventory for estimating volatile emissions from natural gas activities.